(untitled) (Journal of Pharmaceutical Negative Results, 2022)
Objective of this study is to evaluate the ethanolic and aqueous extracts of aerial parts of Pisonia alba for anti-inflammatory and antiulcer activities. Anti-inflammatory action of the ethanolic and aqueous extracts of P. alba (100 and 200 mg/kg b.w.) (EEPA and AEPA) were evaluated by cotton pellet granuloma models. Pylorus ligation and aspirin induced ulcer models were employed for evaluating antiulcer activity for both the extracts. Ulcerogenic potential of PA was also evaluated. The ethanolic and aqueous extracts of P. alba significantly decreased (P<0.01) the granuloma tissue development. EEPA and AEPA at both the doses exhibited significant (P<0.01) antiulcer activity by decreasing the ulcer score in both the ulcer models and it was not ulcerogenic. The ethanolic and aqueous extracts of aerial parts of P. alba (EEPA and AEPA) possess significant antiinflammatory and antiulcer activities.